2020
DOI: 10.1002/adfm.202002570
|View full text |Cite
|
Sign up to set email alerts
|

Light Out‐Coupling Management in Perovskite LEDs—What Can We Learn from the Past?

Abstract: The research on perovskite light‐emitting diodes (PeLEDs) has experienced an exponential growth in the past six years. The highest external quantum efficiencies (EQEs) have surpassed 20%, 20%, and 10% for red, green, and blue colored LEDs, respectively. Considering the internal quantum efficiency is already approaching unity owing to the high material quality, the limiting factor for further improving the EQE is mainly the poor light out‐coupling efficiencies. Here, by reviewing the progress on the light out‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 306 publications
(178 reference statements)
0
49
0
Order By: Relevance
“…In planar LEDs, it is a big challenge to enhance the light out-coupling efficiency due to the various permittivities of dielectric and metal thin film multilayers, which result in near 80% of the light generated by the emitters being trapped inside the device. [129,130] Thus, there is a strong aspiration to improve the device performance by enhancing the light out-coupling efficiency. The construction of periodic micro-nanostructures on the device was accepted as an efficient way to improve the light out-coupling efficiency.…”
Section: Strategies For Light Out-coupling Device Structurementioning
confidence: 99%
“…In planar LEDs, it is a big challenge to enhance the light out-coupling efficiency due to the various permittivities of dielectric and metal thin film multilayers, which result in near 80% of the light generated by the emitters being trapped inside the device. [129,130] Thus, there is a strong aspiration to improve the device performance by enhancing the light out-coupling efficiency. The construction of periodic micro-nanostructures on the device was accepted as an efficient way to improve the light out-coupling efficiency.…”
Section: Strategies For Light Out-coupling Device Structurementioning
confidence: 99%
“…[ 87 ] Meng et al demonstrated that the device structure consisting of transparent electrode/high‐index transport layer/perovskite emitter/low‐index transport layer/reflective electrode could raise η out to 12.0%, 17.5%, and 31.2% for blue, green, and red PeLEDs by reducing the optical loss in surface plasmon and waveguide mode. [ 86 ] Therefore, the low η out leaves considerable opportunity for a substantial boost in EQE of blue PeLEDs if the optical loss can be efficiently suppressed, including waveguide mode, [ 86,88–97 ] surface plasmon mode, [ 98–105 ] and substrate mode. [ 101 ]…”
Section: Challenges and Strategies For Blue Peledsmentioning
confidence: 99%
“…Many techniques have been implemented for the light outcoupling enhancement for various LED technologies, including the use of photonic structure at the appropriate device interfaces, refractive‐index coupling layers, microlens arrays, diffraction gratings, and so on. [ 86,88–107 ] Jeon et al used a randomly distributed nanohole array (NHA) embedded in a SiN x layer between ITO and glass substrate to facilitate the outcoupling of the waveguide mode ( Figure a). [ 106 ] High‐efficiency red/near‐infrared PeLEDs with an EQE max of 14.6% were realized (Figure 6b).…”
Section: Challenges and Strategies For Blue Peledsmentioning
confidence: 99%
“…Apart from material and structure optimization, different approaches are widely explored to improve the quality and performance of PeLEDs, including recent advances in nanophotonics [ 16 , 17 , 18 ]. For example, surface patterning leads to enhanced light outcoupling and photon recycling [ 19 , 20 , 21 , 22 , 23 ] which is beneficial for PeLEDs.…”
Section: Introductionmentioning
confidence: 99%